Implementation of Religious Moderation Through the Tri Dharma of Higher Education - Ifendi, Mahfud; Mubaidilla, Miftakhul Rizal (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study examines the implementation of religious moderation through the Tri Dharma of Higher Education at State Islamic University (UIN) Raden Intan Lampung, which was recognized by the Ministry of Religion as the most responsive Islamic higher education institution in strengthening religious moderation. Using a qualitative descriptive approach with field research methods, this study involves structural officials, lecturers, education staff, and students as research subjects. Researchers interviewed to Head, dean, lecturers, students, and human resources of UIN Raden Intan Lampung. They were as primaries data in this research. Then, the data were collected through interviews, observations, documentation, and literature review, and then analyzed using Miles and Huberman's data analysis technique. The findings reveal that UIN Raden Intan Lampung implements religious moderation comprehensively across three pillars: (1) in education and teaching, moderation values are integrated into all courses through formal approaches (Training of Trainers and seminars) and informal approaches (Islamic holiday commemorations, workshops, and Ma'had coaching programs); (2) in research, a special cluster on pluralism and diversity was established through Rector's Decree No. 288 of 2020, producing scientific publications that strengthen moderate narratives and counter intolerant discourse; (3) in community service, programs such as Religious Moderation Community Service Program (KKN), Ramadan Safari, and Melayu Serumpun KKN serve as effective platforms for disseminating tolerance values directly to diverse communities. This study concludes that the holistic integration of religious moderation through the Tri Dharma framework successfully transforms students into agents of social change who promote harmony, tolerance, and inclusivity, thereby establishing universities as catalysts for social transformation amidst Indonesia's diversity.